When arbitration clause and oppression claim collide - Mohd. Sulaiman, Aiman @ Nariman; Hingun, Mohsin (Routledge Taylor & Francis Group, 2017)
The question regarding the position of arbitration clauses within the context of shareholders’ protection under company law rules has been dealt with in a decision from the United Kingdom, Exeter, which upheld the inalienable right of the members to bring an oppression claim despite the presence of an arbitration agreement. The issue was recently revisited in several common law jurisdictions – United Kingdom, Malaysia, Singapore and Hong Kong with mixed results. The article discusses this development to clarify the scope, breadth and limits of the arbitration clause within company law.